Oscar Wilde - Laver, James (Writers and Their Work Series., 1968)
More has been written about Wilde, since his death, than about writers with thrice his output. Through this forest of comment James Laver cleaves a swift way. He summarizes Wilde's background and achievement and analyses what is most significant in his work. 'As a literary-historical figure, Wilde is unique', he concludes. 'Without him neither the Aesthetic Movement of the 'eighties, nor the Decadent Movement of the 'nineties, can be understood. He has his pe.